The Nature of the Physics of Matter with Negative Mass - Golovkin, BG (Annals of Mathematics and Physics, 2024)
The formation of a substance with negative mass (negamatter) at very high temperatures or body speeds above 235696.8871 km/s is theoretically justified. The reason for this is the reversal of the direction of time inside the substance. The law of dependence of body weight on the rate of time passing in the physical body has been derived. Based on the weakness of gravitational forces, the stability of negamatter is justified, under appropriate conditions.